Study of mono firing process applied to porcelain - Merleau, Audrey Alexandra (2017)
Porcelain production traditionally requires two main firing steps at high temperature, to get its final properties. The first firing, called biscuit firing, is realized at 1000 °C whereas the second firing, called glost firing is performed at 1380 °C. Skipping the biscuit firing represents an important saving of costs and time for porcelain companies. The cost reduction relative to the removal of the biscuit firing has been estimated at 5% of the total production cost. In addition, this industrial modification in the porcelain manufacture will also have a great environmental impact by reducing the fuel consumption. Within this context, this study tested mono-firing process directly on the production line of Porcelanas da Costa Verde SA company. Problems encountered during mono-firing of slip casting, roller jiggering and pressed objects were identified and listed for the first time. The chosen systematic approach allows to identify the main difficulties encountered during the processing, that were mainly related with glazing and the finishing steps. Moreover, it was also verified that the number and type of defects observed on the porcelain pieces depend on the shaping process used upstream such as slip casting, roller jiggering and pressing. When considering the glazing step, experiments clearly show that the green body absorbs less water and glaze than the biscuit. This observation was not expected and argues in favor of differences at the level of porosity and porosity distribution between the green body and the biscuit. It is proposed that although the porosity in the green body is high, it is mainly composed of very small pores. Biscuit pieces are denser due to the initial sintering stages in which the neck formation Study of mono-firing process applied to Porcelain vii between the grains takes place. This initial densification is enough to confer the required mechanical strength to handle the biscuit pieces. However, though the porosity decreases after the first firing, the size of some pores may increase, forming porosity channels open up to the surface, when compared to the green pieces. This phenomenon occurs in response of the 1st sintering realized at 1000 °C. It is then suggested that this different porosity development directly impacts the difference in glaze and water absorption. The presence of the channels at the surface of the biscuit will allow a better penetration of the water and a better adhesion of the glaze. On the contrary, the small pores present in the green body do not promote this penetration of water and adhesion of glaze. Although the absence of high quality microstructures, the obtained results, that show a consistence and same trend for all the shaping processes under study, indicating that despite a high porosity the green bodies remains almost impermeable to water and glaze. Our results clearly show that besides the weak mechanical strengthen of the green bodies, that affects directly handling and finishing steps during mono-firing, the different porosity development also contributes to the differences between mono-firing and bi-firing process of porcelain, in particular at the level of glazing. Concerning the industrial point of view, to reduce the appearance of aspect defects (cracks, bumps) during glazing, and to allow a better glaze adhesion at the surface of the green body a glazing study with glazes with different densities was conducted in the mono-fired pieces. When using a high density of the glaze suspension the final properties and appearance of mono-fired Costa Verde porcelain are very comparable to the aspect and properties of bi-fired one. The results obtained in this work though preliminary are very encouraging towards the substitution of a bi-firing cycle to a mono-firing cycle in porcelanas da Costa Verde, SA.